The ‘P-word’ in Indian juvenile justice: Toward a deeper understanding of legal rhetoric and practice - Prasad, Pupul Dutta (Punishment & society, 2025)
Although the Indian juvenile justice statute is rhetorically silent about punishment, nonetheless recognisably punitive ideas and practices remain ubiquitous. Standard interpretations do not go beyond legal analyses of the mismatch between discourse and practice. However, interviews with policymakers and practitioners arrayed throughout the juvenile justice field in India reveal the need for a nuanced and deeper understanding of legal rhetoric and practice. A more rigorous, qualitative analysis of penal practices foregrounds the interplay between a set of enabling factors that include, but are not limited to, social constructions of childhood deviance, and attitudes and interests of key juvenile justice actors. It also accounts for why Indian juvenile justice actors euphemise punishment as if it were an unspeakable ‘p-word’, while reinscribing punishment as a normal and normative objective to pursue.